Fashion and aging: body changes and comfort in clothing (PerCursos, 2024)
Due to the perspective on the increase in the number of elderly people, consequently, there is a growing demand for products that meet the ergonomic needs arising from advancing age. With that, the objective of this work is to analyze the corporal changes of the elderly women and the comfort of the clothes for this public, aiming at the four fundamental aspects of the total comfort of the clothes. To do so, female aging and the bodily changes that occur with advancing age will be conceptualized, as well as describing the concepts that comprise the four fundamental pillars of comfort. As for the methodology, the present research is of an applied nature and with an exploratory character. It was based on a bibliographic review of books, articles and reports. The methodology used was qualitative and quantitative field research. At the end of this study, we can see that the clothes made for this niche do not comply with the four fundamental pillars of comfort.
Keywords: aging; comfort; fashion